Understanding Metabolic Syndrome and its Nutritional Management - Gulafsha Shakir; Bushra Shaida (International Journal of Sustainability, 2025)
Metabolic syndrome (MetS) is a collection of risk factors, especially when at least three occur together, including abdominal obesity, dyslipidemia, low high-density lipoprotein cholesterol (HDL-c) levels, hypertension, and insulin resistance. MetS is linked to an increased risk of diabetes and cardiovascular diseases (CVDs) if treatment is not received.The causes of MetS include both genetic and acquired factors that contribute to issues such as insulin resistance, chronic low-grade inflammation, and obesity. One of the primary approaches to treating and managing metabolic syndrome is through lifestyle modifications, particularly changes in dietary habits. Although the most effective dietary strategy has yet to be determined, specific dietary adjustments such as upgrading the quality of the food or modifying distribution of macronutrients in the food, have shown helpful results in managing metabolic syndrome conditions. However, energy-specific dietary practices and scaling down physical inactivity are essential in improving metabolic disturbances thus in the present review detailed risk factors and management of metabolic syndrome will be discussed.
Keywords: Insulin Resistance; abdominal obesity; dietary patterns; management; metabolic syndrome; nutraceuticals